The homeodomain protein Nanog and pluripotency in mouse embryonic stem cells. (26th October 2005) - Yates, A.; Chambers, I.
Abstract : Intrinsic regulators of the pluripotency of mouse ES (embryonic stem) cells include the homeodomain proteins Oct4 and the recently identified Nanog. When overexpressed, Nanog displays the unique attribute of robustly sustaining ES cell self-renewal in the absence of the otherwise requisite extracellular stimulation by LIF (leukaemia inhibitory factor) and BMP (bone morphogenetic protein). Here, we review our current understanding of the function of Nanog in pluripotent stem cells both in vitro and in vivo .